Hubungan Konsep Diri Dengan Penerimaan Diri Pasien Kanker Payudara - Merlin, Ni Made; Toba, Yulianti; Pandie, Fance Roynaldo; Vanchapo, Antonius Rino (Jurnal Kesehatan, 2021)
Breast cancer is one of the most common types of disease in women. The number of breast cancer incidence is always increasing every year. Breast cancer can cause several psychological complaints, one of which is self-acceptance and self-concept. Purpose: the purpose of this study was to see the relationship between self-concept and self-acceptance of breast cancer patients. The study design was cross-sectional with a consecutive sampling technique. This study was conducted in the I inpatient room at the RSUD. Prof. Dr. W.Z. Johannes Kupang. The number of respondents in this study was 50 patients. The statistical test used is chi-square. 25 patients with breast cancer in inpatient room who experienced negative self-concept, most of the breast cancer patients experienced moderate self-acceptance as many as 26 people, statistical test results obtained p-value 0,01. There is a relationship between self-concept and self-acceptance of breast cancer patients indicated by a p-value<0,05.